Remodeling of periorbital, temporal, glabellar, and crow's feet areas with hyaluronic acid and botulinum toxin. (June 2014) - Beer, Kenneth R; Julius, Hillary; Dunn, Monica; Wilson, Fred
Summary Botulinum toxins are currently used to reduce facial muscle activity, and hyaluronic acid is used to correct volume loss. This study evaluates the combination of abobotulinumtoxinA (Dysport) and hyaluronic acid 20 mg/mL (Perlane) for rejuvenating specific areas of the upper face. Subjects (n = 20) with mild to moderate temporal volume loss as well as glabellar and/or periorbital rhytids were enrolled in this single‐center, open‐label, nonrandomized pilot study. Subjects were randomly assigned a number and treated with hyaluronic acid, divided between temporal and glabellar region, and abobotulinumtoxinA in the periorbital and glabellar region. A 1‐month touch‐up was given if needed. Subjects were evaluated by the investigator, and each subject completed a questionnaire at baseline and at 3, 6, and 9 months after treatment. For glabellar lines and crow's feet, median grades decreased from baseline at 1 month and at 3 months, but returned to baseline values at 6 months. For temporal assessments, the median grade decreased from baseline at 1, 3, and 6 months and returned to baseline at 9 months. Similar trends were observed in subjects' perceived age, perceived social and professional limitations, and desire to alter their facial appearance. Among subjects previously treated with botulinum toxin alone, 64% rated the combination treatment said "superior." Adverse effects were mild and transient. The combination of abobotulinumtoxinA and hyaluronic acid appears to rejuvenate the periorbital, temporal, glabellar, and crow's feet areas with minimal adverse effects.